Trends in practice patterns and outcomes: A decade of sarcoma care in the United States. (June 2019) - Song, Yun; Ecker, Brett L.; Tang, Rebecca; Maggino, Laura; Roses, Robert E.; DeMatteo, Ronald P.; Fraker, Douglas L.; Karakousis, Giorgos C.
Abstract: Background: Soft tissue sarcomas (STS) represent a rare and heterogeneous group of tumors. We sought to characterize national trends in referral patterns, treatment strategies, and overall survival (OS) over the course of a decade. Methods: Adult patients with extra-abdominal STS were identified using the National Cancer Database and categorized by diagnosis year (2005–2009 and 2010–2014). High-volume hospitals (HVH) were defined as those >90 th percentile in volume of STS patients treated, and others were defined as low-volume hospitals (LVH). Standard statistical methods were used to compare treatment strategies and OS by diagnosis period. Results: Of 55, 212 patients, 25, 469 (46.1%) were diagnosed in 2005–2009 and 29, 743 (53.9%) in 2010–2014. Despite increased utilization of neoadjuvant radiation therapy (26.6% vs. 34.8%, P < 0.001), the rate of R0 resections did not change (75.0% vs. 74.8%, P = 0.067). Furthermore, at a national level, OS did not improve over time (HR 0.99, 95% CI 0.96–1.01). When outcomes were stratified by volume, treatment at HVH compared to LVH was associated with improved rates of R0 resection (OR 1.27, 95% CI 1.20–1.35) and OS (HR 0.92, 95% CI 0.89–0.95). Moreover, there was a modest improvement in OS at HVH (HR 0.95, 95% CI 0.91–1.00), but not at LVH (HR 1.01, 95% CI 0.97–1.04). However, referral to HVH did not change over time (40.7% vs. 40.7%, P = 0.91). Conclusion: OS for STS did not change at a national level over the course of a decade, although it improved at HVH. Further outcome improvements will likely require more effective systemic therapies. Highlights: Soft tissue sarcomas (STS) represent a heterogeneous group of mesenchymal tumors. Neoadjuvant administration of radiation therapy for resectable STS has increased. There has been a modest improvement in survival in patients treated at high-volume sarcoma centers. Survival outcomes at low-volume centers remain unchanged. More effective therapies for STS are needed to make a substantial impact on survival.